In-situ investigation of Hf6Ta2O17 anisotropic thermal expansion and topotactic, peritectic transformation. (December 2018) - McCormack, Scott J.; Weber, Richard J.; Kriven, Waltraud M.
Abstract: The anisotropic coefficients of thermal expansion and the peritectic transformation of orthorhombic-Hf6 Ta2 O17 to tetragonal-HfO2 plus liquid at 2250 °C have been studied by in-situ X-ray powder diffraction from room temperature to complete melting (∼2450 °C) in air, using a quadrupole lamp furnace (QLF) and a conical nozzle levitator (CNL) equipped with a CO2 laser. The topotactic, peritectic transformation has been fully described by extracting the orientation relationship, lattice variant deformation and a motif (grouping) of cations that relates the two structures at the transformation temperature. The calculation of these two important parameters as well as identification of the motif is facilitated by a knowledge of the anisotropic coefficients of thermal expansion as a function of temperature. Symmetry decomposition has been performed to show that the orthorhombic-Hf6 Ta2 O17 and tetragonal-HfO2 structures are simply related by polyhedral rotations and loss of 1 mol of oxygen. Graphical abstract: Image 1